2010
DOI: 10.2166/wst.2010.388
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of anionic dyes in aqueous solution using chemically modified barley straw

Abstract: An agricultural waste derived adsorbent was prepared by chemically modified barley straw with NaOH and a cationic surfactant hexadecylpyridinium chloride monohydrate (CPC). The prepared adsorbent, BMBS, was used for removal of anionic dyes; Acid Blue (AB40) and Reactive Blue 4 (RB4) from aqueous solution in a batch adsorption system. The adsorbent was characterized by FT-IR and elemental composition. The stability of CPC adsorbed on straw surface was also evaluated by exposing to aqueous solution. In adsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…The mechanism for the removal of MB by adsorption may be due to the migration of dye from the bulk of the solution to the surface of the adsorbent, diffusion of dye through the boundary layer to the surface, adsorption of dye at active sites on the surface of adsorbent and intraparticle diffusion of dye into the interior pore structure of the adsorbent. The boundary layer resistance may be affected by the rate of adsorption and increase in contact time, which may increase the mobility of dye species during adsorption [7,[58][59][60][61][62][63][64][65][66][67].…”
Section: Adsorption Mechanismmentioning
confidence: 99%
“…The mechanism for the removal of MB by adsorption may be due to the migration of dye from the bulk of the solution to the surface of the adsorbent, diffusion of dye through the boundary layer to the surface, adsorption of dye at active sites on the surface of adsorbent and intraparticle diffusion of dye into the interior pore structure of the adsorbent. The boundary layer resistance may be affected by the rate of adsorption and increase in contact time, which may increase the mobility of dye species during adsorption [7,[58][59][60][61][62][63][64][65][66][67].…”
Section: Adsorption Mechanismmentioning
confidence: 99%
“…In recent years, many studies have suggested that waste plant materials can be utilized as potential sources of cheap and easily available biosorbents for organic dyes, heavy metal ions, radionuclides or endocrine disruptors. Plant derivatives, such as wheat straw, barley straw, rice straw, spent grain, pumpkin husks, peanut husks, spent coffee grounds, spent tea leaves, sawdust, sugarcane bagasse and many others, have been successfully used for adsorption of water‐soluble organic dyes from water systems.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have been trying to find ways to take advantages of straw [14,15]. One of the promising ways to use this precious bioresource is to produce straw-based adsorbents [16][17][18][19][20]. However, the adsorption capacity of unmodified straw is insignificant, since straw materials are deficient in free ionic groups, which would play an important role in removal of ionic dyes.…”
Section: Introductionmentioning
confidence: 99%